TARIYXÍY-MÁDENIY MIYRASLARDÍ QORǴAW – KONSTITUCIYALÍQ MINNET - Tilewov, E.; Dosmaganbetov, S. (ILIM hám JÁMIYET, 2024)
In the article, the cultural heritage objects (tangible and intangible cultural heritage objects), which are the national wealth of the people of Uzbekistan, and the constitutional legal basis of their protection were widely explained.